Pengaruh Ukuran Serbuk Pada Aktivasi Tanah Liat Dari Tanak Awu Terhadap Daya Adsorpsinya Pada Pemurnian Minyak Goreng Bekas - Nufida, Baiq Asma; Kurnia, Nova; Kurniasih, Yeti (Hydrogen: Jurnal Kependidikan Kimia, 2014)
This research was aimed to get the effect of particel size of activated natural clay from Tanak Awu to their adsorption capacity for increase reused cooking oil quality. At previous research we done the activation of natural clay using acid (HCl) and got an optimal concentration of acid at 1 molar. Natural clay was grinding until particel size at 50 mesh, 60 mesh and 100 mesh then it was characterized in specific surface area by methylen blue methods and also acidity surface by acid base titration. Then activated natural clay was applied for purifying reused cooking oil by analyzing water content, acid number and peroxide number. The result showed that there are the effect of particel size of natural clay to acidity surface and specific surface area. While the adsorption capacity of natural clay on purifying reused cooking oil got that optimal particel size of activated natural clay at 60 mesh which getting the decrease of water content, acid number and peroxide number by following reach was 89,13%, 58,61% and 60,52%.